ROLE AND ELEVATING PROGNOSTIC PRECISION OF PIVKA-II AS A SUPERIOR BIOMARKER IN HCC DIAGNOSIS, SURPASSING AFP - YASEEN , M; ANWAR , R; AHMAD , MM; JAVAID , H; SADIA , M; BUTT , MR (Biological and Clinical Sciences Research Journal, 2024)
The objective of this study was to evaluate the diagnostic accuracy of PIVKA-II as compared to AFP for the detection of hepatocellular carcinoma (HCC) and its potential as a devoid prognostic biomarker. With genomic discoveries, including gene mutations, epigenetic alterations, and non-coding RNAs, the context around HCC biomarkers has increased. The relevance of prognostic and predictive biomarkers is growing as they support treatment choices and evaluate clinical outcomes. These indicators are significant tools in enhancing patient care because they improve diagnosis, direct therapy, forecast outcomes, and evaluate treatment responses. Comprehensive information on the predictive value of several markers, however, is still lacking. In this study, 85 people took part, including those older than 18 with hepatocellular carcinoma in a range of clinical stages. Three groups represented the study population, comprising 85 individuals in total: group 1 consisted solely of patients with HCC, group 2 included patients with benign liver disease, and group 3 was designated as the control group. A male predominance is found in groups, except group 2. The quantity of PIVKA-II in serum was measured using an automated analyzer that was based on the CMIA. The immunoassay method was applied to determine the concentration of AFP. The statistical analyses of PIVKA-II and AFP consisted of sensitivity 90–99% and 58–81%, specificity 68–99%, and 61–98% with a 95% CI, respectively. The findings emphasize PIVKA-II’s superior performance as a biomarker of cancer response when compared to AFP.